The Effectiveness of Massage Therapy on Pain Reduction in Rheumatoid Arthritis Patients: Literature Review - Achlish Abdillah; Syaifuddin Kurnianto; Meylinda Rizky Wahyuni (KHD Production, 2023)
Rheumatoid Arthritis is a chronic inflammatory disease that can cause bone damage and cause disability. The most common and dominant symptom is pain, especially swelling in the morning. There is a way to treat pain in rheumatoid arthritis patients with massage. Massage has the effect of reducing anxiety and muscle tension. This muscle massage stimulation is enriched to stimulate delta-A nerve fibers and C fibers and releases substance P in the afferent nerves, where there are mechanoreceptors (tactile apparatus: skin) as a defense mechanism, and in the central cortex, the descending nerves release endogenous. opiates, namely endorphins produced by the pituitary as a pain reliever. So, it can block or reduce pain impulses. This study aims to determine the effect of massage on reducing pain intensity in rheumatoid arthritis patients. This research uses a literature review design using 2 databases, namely PubMed and Scopus. The results showed that in journal research, giving massage for ± 15 minutes every day resulted in reduced pain and anxiety. In the journal, rheumatoid arthritis sufferers had a decrease in the quality of pain using back massage therapy with p=0.05. The conclusion of this study shows that the use of massage therapy is effective for patients with rheumatoid arthritis who experience pain.